Patterns of Toll-Like Receptor Expressions and Inflammatory Cytokine Levels and Their Implications in the Progress of Insulin Resistance and Diabetic Nephropathy in Type 2 Diabetic Patients - Aly, Rofyda H.; Ahmed, Amr E.; Hozayen, Walaa G.; Rabea, Alaa Mohamed; Ali, Tarek M.; El Askary, Ahmad; Ahmed, Osama M. (Frontiers in Physiology, 2020)
Abstract Background: Diabetic nephropathy (DNP) is a type 2 diabetes mellitus (T2DM) chronic complication, which is the largest single cause of end-stage kidney disease. There is an increasing evidence of the role of inflammation and Toll-like receptors (TLRs) as part of innate immune system in its development and progression. In addition, Toll-like receptor 2 (TLR2) and Toll-like receptor 4 (TLR4) downward signaling causes the production of proinflammatory cytokines, which can induce insulin resistance in T2DM. Objective: The goal of this study was to estimate the expression of TLRs (TLR2 and TLR4) in relation to inflammation and insulin resistance in nephrotic type 2 diabetic patients with or without renal failure and to discuss the role of these TLRs in DNP progression. Patients and methods: In this study, blood samples were obtained from type 2 diabetic patients with or without renal failure, and patients with non-diabetic renal failure were compared to healthy controls. All participants were tested for analysis of fasting plasma glucose and serum insulin, kidney function tests, C-reactive protein (CRP), and pro-inflammatory cytokines including tumor necrosis factor alpha (TNF-α), interferon gamma (IFN-γ) and interleukin 6 (IL-6) as well as expression of TLR2 and TLR4 in peripheral blood. Statistical analysis of data was done by using SPSS. Results: Diabetic patients with renal failure exhibited significant increase in TLR2, TLR4 mRNA expression in peripheral blood in comparison with normal subjects, diabetic patients without renal failure and non-diabetic patients with renal failure. Both diabetic patients with or without kidney failure and non-diabetic patients with renal failure had increased TLR2 and TLR4 mRNA expression in association with increased levels of proinflammatory cytokines (TNF-α , IFN-γ and IL-6) compared to normal subjects. The diabetic patients with kidney failure exhibited the highest elevation of TLRs, Th1 cytokines and CRP in association the highest record of insulin resistance. Conclusion: TLR2 and TLR4 increased expression and Th2 cytokines may have an important role in the progression of DNP and deteriorations in insulin resistance in type 2 diabetic patients. Therefore, TLR2 and TLR4 may be a promising therapeutic target to prevent or retard DNP in type 2 diabetic patients.